Scotland's enduring eclectic Classicism - Campbell, Ian 1953- (2020)
The appreciation of the influence of classicism on Scottish architecture has been bedevilled for centuries by historians regarding it in a British context, in which it appears aberrant compared with English architecture. Classical influence in Scottish architecture is still commonly thought to only begin in the late seventeenth century. Here, instead, it will be argued that the Renaissance arrived in Scotland before England, but it manifested itself in manners which went unrecognised until recently. Scotland’s attitude to classicism was conditioned by three factors. One is the fact that it was never conquered by the Romans; another is its mediaeval origin myth that the Scots descend from a pharaoh’s daughter and an Athenian prince; the third is its greater openness to continental influence, especially the ‘Auld Alliance’ with France, which meant that the Scots looked far more to the continent than England did for centuries.
Keywords: Geschichte; Rezeption; Antike; Architektur; Renaissance; Schottland